2018
DOI: 10.20944/preprints201803.0047.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Human Sustainability of ICT and Management Changes: Evidence for the French Public and Private Sectors

Abstract: We investigate the human sustainability of ICT and management changes using a French linked employer-employee survey on organizational changes and computerization (COI). We approach the human sustainability of changes through the evolutions of work intensity, skill utilization and the subjective relationship to work. We compare in the private sector and the State civil service the impacts of ICT and management changes on the evolution of these three dimensions of work experience. We find that when ICT and mana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several pieces of empirical evidence testify to a positive association between computerized and/or automated technologies and work intensity (Green and McIntosh 2001; Green 2006; Chesley 2014; Bigi, Greenan, Hamon-Cholet, and Lanfranchi 2018; Felstead, Gallie, Green, and Henseke 2019). Bittman, Brown, and Wajcman (2009) found that mobile phones at work intensified the work of men, though not of women, in a sample of Australian workers.…”
Section: Work Intensity and Work Intensificationmentioning
confidence: 99%
“…Several pieces of empirical evidence testify to a positive association between computerized and/or automated technologies and work intensity (Green and McIntosh 2001; Green 2006; Chesley 2014; Bigi, Greenan, Hamon-Cholet, and Lanfranchi 2018; Felstead, Gallie, Green, and Henseke 2019). Bittman, Brown, and Wajcman (2009) found that mobile phones at work intensified the work of men, though not of women, in a sample of Australian workers.…”
Section: Work Intensity and Work Intensificationmentioning
confidence: 99%